Prognostic Implications of Resistive Reserve Ratio in Patients With Nonobstructive Coronary Artery Disease With Myocardial Bridging - Negin Mahmoudi Hamidabad; Yoshihisa Kanaji; Ilke Ozcan; Jaskanwal Deep Singh Sara; Ali Ahmad; Lilach O. Lerman; Amir Lerman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Myocardial bridging (MB) is accompanied by the dynamic extravascular compression of epicardial coronary arteries, leading to intracoronary hemodynamic disturbance with abnormal coronary flow profiles. We aimed to evaluate the prognostic implications of resistive reserve ratio (RRR), a composite measure of flow and pressure parameters that represents the vasodilatory capacity of the coronary arteries, in patients with angina with nonobstructive coronary artery disease (ANOCA) and MB, in comparison with coronary flow reserve (CFR). Methods and Results In this retrospective cohort study, we included patients with ANOCA who underwent coronary reactivity testing, where MB was identified by transient constriction in coronary artery segments between systole and diastole. Abnormal CFR and RRR were defined as <2.5 and <2.62, respectively. Major adverse cardiac events, including cardiovascular death, stroke, myocardial infarction, heart failure, and late revascularization, served as outcomes. Among 1251 patients with ANOCA, 191 (15.3%) had MB. The prevalence of abnormal CFR or RRR was not significantly different between patients with and without MB (P=0.144 and P=0.398, respectively). Over a median follow‐up time of 6.9 years, abnormal RRR predicted major adverse cardiac events in patients with MB (hazard ratio [HR], 4.38 [95% CI, 1.71–11.21]; P=0.002) and without MB (HR, 1.91 [95% CI, 1.38–2.64]; P<0.001). Abnormal CFR predicted major adverse cardiac events in patients without MB (HR, 2.15 [95% CI, 1.54–3.00]; P<0.001), whereas it was not predictive of major adverse cardiac events in patients with MB (HR, 2.29 [95% CI, 0.93–5.65]; P=0.073). Conclusions In patients with ANOCA and MB, impaired RRR was superior to impaired CFR in distinguishing patients at a higher risk of future adverse events, suggesting that RRR may serve as a risk stratification tool in patients with MB and ANOCA.